Is trade liberalization necessary pre-condition for good growth? - Nwachukwu Dimkpa Damian. (2008)
This dissertation tries to examine if trade liberalization is a necessary pre-condition for good growth, and if not, what other factors would considered the necessary pre-conditions for good growth in a developing economy. The good growth registered by some closed economies raised the question on trade liberalization as a necessary pre-condition for good growth.